Synthesis and Decontamination Effect on Chemical and Biological Agents of Benzoxonium-Like Salts - Aneta Markova; Michaela Hympanova; Marek Matula; Lukas Prchal; Radek Sleha; Marketa Benkova; Lenka Pulkrabkova; Ondrej Soukup; Zuzana Krocova; Daniel Jun; Jan Marek (Toxics, 2021)
Benzoxonium chloride belongs to the group of quaternary ammonium salts, which have been widely used for decades as disinfectants because of their high efficacy, low toxicity, and thermal stability. In this study, we have prepared the C10-C18 set of benzoxonium-like salts to evaluate the effect of their chemical and biological decontamination capabilities. In particular, biocidal activity against a panel of bacterial strains including Staphylococcus aureus in biofilm form was screened. In addition, the most promising compounds were successfully tested against Francisella tularensis as a representative of potential biological warfare agents. From a point of view of chemical warfare protection, the efficiency of BOC-like compounds to degrade the organophosphate simulant fenitrothion was examined. Notwithstanding that no single compound with universal effectiveness was identified, a mixture of only two compounds from this group would be able to satisfactorily cover the proposed decontamination spectrum. In addition, the compounds were evaluated for their cytotoxicity as a basic safety parameter for potential use in practice. In summary, the dual effect on chemical and biological agents of benzoxonium-like salts offer attractive potential as active components of decontamination mixtures in the case of a terrorist threat or chemical or biological accidents.